2018
DOI: 10.1891/1933-3196.12.2.58
|View full text |Cite
|
Sign up to set email alerts
|

EMDR-Based Divorce Recovery Group: A Case Study

Abstract: This case study investigated the effects of an eye movement desensitization and reprocessing (EMDR)-based divorce recovery group, consisting of four modalities: (a) modified EMDR Integrative Group Treatment Protocol adapted for adolescents and adults living with ongoing traumatic stress (EMDR-IGTP-OTS) to deal with the trauma from the divorce, (b) modified Affect Circuit Reset protocol to reduce intensity of negative affects, (c) psychoeducation on affects and divorce-related issues, and (d) small group discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…Shapiro, 2001). In another study conducted using EMDR in group therapy, group members reported that they learned from each other, had a decreased sense of loneliness, and a greater sense of belonging (Wong, 2018). In light of the above, the Online EMDR Group Traumatic Episode Protocol (i-GTEP) was believed to be effective in terms of the satisfaction of psychological needs and the relevant subcategories.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Shapiro, 2001). In another study conducted using EMDR in group therapy, group members reported that they learned from each other, had a decreased sense of loneliness, and a greater sense of belonging (Wong, 2018). In light of the above, the Online EMDR Group Traumatic Episode Protocol (i-GTEP) was believed to be effective in terms of the satisfaction of psychological needs and the relevant subcategories.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Des adaptations culturelles des protocoles EMDR individuels et de groupe ont été décrites par des thérapeutes et des chercheurs d'Asie, d'Europe, du Moyen-Orient et d'Amérique du Nord et du Sud (Acarturk et coll., 2015;Allon, 2015;Hurn & Barron, 2018;Jarero et coll., 2014;Lehnung et coll., 2017;Mehrotra, 2014;Rasolkhani-Kalhorn, 2005;Seponski, 2011;Ter Heide et coll., 2014 ;Woo, 2014). L'EMDR-IGTP a également été utilisé avec succès avec des enfants et des adultes dans divers contextes à faibles ressources (Artigas et coll., 2014;Jarero & Artigas, 2012;Wong, 2018).…”
Section: Modifications Culturelles De L'emdrunclassified
“…Farklı kuramsal yönelimlere dayanan ve grup yaklaşımını temel alan müdahalelerin boşanma sürecinde etkililiğini test eden araştırmalar bulunmaktadır. Boşanma sürecinde psikolojik müdahale olarak öyküsel terapi yaklaşımının (Pietsch, 2000), birer saatlik yirmi oturumu içeren şema terapi yaklaşımının (Panahifar ve diğerleri, 2014), on grup oturumu içeren Satir'in yaklaşımının (Asghar, 2017), ikişer saatlik on grup oturumunu içeren Fisher'ın yaklaşımının (Asanjarani ve diğerleri, 2018), doksan dakikalık sekiz grup oturumunu içeren Gottman yaklaşımının (Mahmoodabadi ve Zarei, 2018), sekiz grup oturumunu içeren EMDR yaklaşımının (Wong, 2018), doksan dakikalık on bir grup oturumunu içeren Kabul ve Kararlılık Terapisi yaklaşımının (Abosaidi-Moghadam ve diğerleri, 2020) ve sekiz grup oturumunu içeren bilinçli farkındalık temelli bilişsel terapi yaklaşımının (Sedighi ve diğerleri, 2021) test edildiği görülmektedir. Araştırma bulgularına göre bu yaklaşımların katılımcıların boşanmayla ilişkili yaşadıkları problemler ve geliştirdikleri yeterlikler açısından anlamlı olarak etkili bulunduğu bildirilmektedir.…”
Section: İlişkili Araştırmalarunclassified